METHEMOGLOBINEMIA-AN ALTERNATIVE TREATMENT MODALITY - Saleem, Muhammad Khurram; Kashif, Muhammad; Javed, Muhammad Waqas; Raza, Abbas; Siddiqui, Arif M (Journal of Ayub Medical College Abbottabad, 2015)
Methaemogloninemia is a rare condition characterized by elevated levels of methemoglobin levels. We report a case of a young lady who took thinner (a solvent used in paint). Methemoglobinemia was diagnosed on the basis of saturation gap and elevated methemoglobin levels. She recovered after exchange transfusion, which was done due to non-availability of parenteral methylene blue. Keywords: Methmoglobinemia, treatment, exchange transfusion